2014
DOI: 10.1038/pr.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of WSB1 isoforms in growth and survival of neuroblastoma cells

Abstract: Our results point to a possible differential role of WSB1 isoforms in NB and suggest WSB1(3) as a target for therapy in NB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…A gene expression analysis of 37 neuroblastoma patients revealed that increased WSB1 copy number correlates with good prognosis (28). In contrast, reduced cell proliferation and enhanced resistance to apoptosis are observed in both pancreatic cancer cells and neuroblastoma cells after WSB1 overexpression (16,29). More recently, data from hepatocellular carcinoma cells further suggest that WSB1 plays a critical role in hypoxia-induced chemoresistance (26).…”
Section: Discussionmentioning
confidence: 99%
“…A gene expression analysis of 37 neuroblastoma patients revealed that increased WSB1 copy number correlates with good prognosis (28). In contrast, reduced cell proliferation and enhanced resistance to apoptosis are observed in both pancreatic cancer cells and neuroblastoma cells after WSB1 overexpression (16,29). More recently, data from hepatocellular carcinoma cells further suggest that WSB1 plays a critical role in hypoxia-induced chemoresistance (26).…”
Section: Discussionmentioning
confidence: 99%
“…And so far there is no report about the role of miRNAs in the expression of WSB1. Given that HIF-1α has been shown to up-regulate WSB1 in HCC combined with the evidence of WSB1 stabilizing HIF-1α [8, 9], there could be a positive feedback loop self-perpetuating the signaling between HIF-1α and WSB1. Because miR-529 presents as the sole upstream regulator of WSB1, it will be possible that mir-592 is a potential key regulator keeping the equilibrium of WSB1/HIF-1α signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains poorly understood about the role of miRNAs in HIF-1α-altered tumor cell metabolism. WD repeat and SOCS box containing 1 (WSB1) was recently identified as a new member of the suppressor of cytokine signaling (SOCS) box protein family, and its expression was upregulated in multiple types of human cancers [8]. More recent evidence suggested that WSB1 is a direct target of HIF-1α in a human HCC model [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of wsb1 expression has been documented in diverse cancer cell types, including neuroblastoma (NB), hepatocellular carcinoma (HCC), pancreatic, osteosarcoma and breast cancer cells [ 1 , 6 , 8 , 23 , 29 , 36 , 37 , 39 ]. Copy number changes of wsb1 can be identified in cases of neuroblastoma.…”
Section: Wsb1 and Cancermentioning
confidence: 99%
“…As reported in Ensembl, the gene encodes for 9 exons, and alternative splicing results in 17 putative transcripts ( http://uswest.ensembl.org/Homo_sapiens/Gene/Summary?db=core;g=ENSG00000109046;r=17:27294076-27315926 ). However, only three major alternative wsb1 transcripts have been reported in the literature [ 1 , 3 , 36 ]. It was shown, through Northern blotting of different human tissues, that the three wsb1 mRNA were highly expressed in the brain, heart, kidney, and placenta [ 3 ].…”
Section: Introductionmentioning
confidence: 99%